Increased prefrontal D2 protein in Tourette syndrome: a postmortem analysis of frontal cortex and striatum - Minzer, Karen; Lee, Olivia; Hong, John J; Singer, Harvey S (Journal of the neurological sciences, 2004)
The precise neuropathological mechanism underlying Tourette syndrome (TS) is unknown. In order to evaluate a variety of proposed dopaminergic abnormalities, postmortem tissue samples were obtained from three individuals with TS (two typical males with childhood onset, ages 29 and 77, and a 62-year-old female with adult-onset) and three age- and sex-matched controls. Samples from caudate, putamen, ventral striatum, and prefrontal cortex (Brodmann's area 9, BA9) were analyzed by semiquantitative immunoblotting for relative densities of dopamine receptors (D1, D2), transporter (DAT), monoamine terminals (vesicular monoamine transporter type 2), vesicular docking and release proteins (VAMP-2, synaptotagmin, SNAP-25, syntaxin, synaptophysin), and receptors inhibiting dopamine release (alpha 2-adrenergic receptors, α-2A). Concentrations of monoamine neurotransmitters and their metabolites were assessed by high performance liquid chromatography. Data from each TS sample was calculated as a percent value of its control. Results showed that prefrontal cortex, rather than striatum, had the greatest number of changes in the two typical TS cases, including increases for D2, DAT, VAMP-2, and α-2A. All three TS subjects had increased densities of prefrontal D2 receptor protein, greater than 140% of their matched control. These results suggest the presence of a prefrontal-dopaminergic abnormality in TS and emphasize the need for a more specific focus on the frontal lobe.